Hubungan Tingkat Kecemasan dengan Kesiapan Dokter Gigi dalam Menghadapi Pandemi Covid-19 - Wilia, Michelle; Prasetya, Mia A.; Rejeki, Putri (e-GiGi, 2021)
Abstract: Coronavirus disease 2019 (Covid-19) can cause respiratory problems and affect all ages. The nature of the transmission and the mortality rate of this viral infection bring about anxiety among health workers, inter alia, dentists because they have a high risk of contracting Covid-19. This study was aimed to determine the relationship between anxiety levels and the preparedness of dentists in facing the Covid-19 pandemic. This was an analytical study with a cross-sectional design. A quantitative study was conducted using a questionnaire that has been structured and tested for its validity and reliability. The questionnaire was divided into two parts, as follows: demographic data and levels of anxiety. Data were analyzed univariately and bivariately with the Spearman correlation test. There were 276 dentists in Bali as respondents who participated in this study. The results showed that the highest level of anxiety was moderate anxiety (54.3%) and there was a relationship between level of anxiety and the number of screening and patient settings with a p-value of 0.034 (p<0.05). In conclusion, there is a relationship between level of anxiety and the dentist's preparedness in the form of number of screening and patient setting to face the Covid-19 pandemic in Bali.Keywords: Covid-19; dentist; anxietyÂ Abstrak: Coronavirus disease 2019 (Covid-19) dapat menyebabkan gangguan pernapasan dan menyerang segala rentang usia. Sifat transmisi dan tingkat mortalitas infeksi virus ini menye-babkan kecemasan di kalangan petugas kesehatan, salah satunya dokter gigi karena memiliki risiko tinggi tertular Covid-19. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat kecemasan dan kesiapan dokter gigi dalam menghadapi pandemi Covid-19 di Bali. Jenis penelitian ialah analitik dengan desain potong lintang. Penelitian kuantitatif dilakukan menggunakan kuesioner yang telah disusun dan diuji validitas dan reliabilitasnya. Kuesioner dibagi menjadi dua bagian yaitu data demografi dan tingkat kecemasan dokter gigi. Hasil data dianalisis secara univariat dan bivariat menggunakan uji korelasi Spearman. Terdapat 276 dokter gigi di Bali yang berpartisipasi dalam penelitian ini. Hasil penelitian menunjukkan bahwa tingkat kecemasan paling tinggi ialah kecemasan sedang (54.3%) dan terdapat hubungan antara tingkat kecemasan dengan jumlah skrining dan pengaturan pasien dalam menghadapi pandemi Covid-19 di Bali dengan p=0,034 (p<0,05). Simpulan penelitian ini ialah terdapat hubungan antara tingkat kecemasan dengan kesiapan dokter gigi yang dinyatakan dalam jumlah skrining dan pengaturan pasien dalam menghadapi pandemi Covid-19 di Bali.Kata kunci: Covid-19; dokter gigi; kecemasan